2016
DOI: 10.5604/08669546.1218793
|View full text |Cite
|
Sign up to set email alerts
|

Drivers’ adaptive travel behaviors towards green transportation development: a critical review

Abstract: The transportation professionals integrated the concept Green in various dimensions of transportation, such as, green vehicle, green highway. The current study has established a new dimension to green transportation, which is called Green Driver as whom substantially contributes to less emission and fuel consumption, and higher-safety. The research established the driver’s Green Adaptive Travel Behaviors (GATB), in particular, that is referred to voluntary personal and lifestyle behaviors on less energy consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Additionally, studies have shown that diesel vehicles consume the most fuel compared to other types of fuel. Therefore, driving style due to inherent drivers' attitudes was one of the major issues of concern [21][22][23][24]. Haworth et al [25] and Majid et al [26] stated that complying with traffic speed limits could lower vehicle fuel consumption.…”
mentioning
confidence: 99%
“…Additionally, studies have shown that diesel vehicles consume the most fuel compared to other types of fuel. Therefore, driving style due to inherent drivers' attitudes was one of the major issues of concern [21][22][23][24]. Haworth et al [25] and Majid et al [26] stated that complying with traffic speed limits could lower vehicle fuel consumption.…”
mentioning
confidence: 99%
“…The study on walkability is a rapidly growing interest that integrates the expertise of several disciplines: transportation planning, urban design and planning, public health, and landscape architecture [69][70][71]. Indeed, urban walkability can safeguard the future performance of green and low-energy urban development by integrating the triple-bottom-line of sustainability [72][73][74]; environment protection (i.e., the environmental aspects of walkability), human well-being and livability (i.e., the social aspects of walkability), and economic sensitiveness (i.e., the economic aspects of walkability).…”
Section: Discussionmentioning
confidence: 99%
“…Since the number of vehicles globally is expected to increase threefold by 2050 (Shafaghat et al, 2016), the need to refocus attention on driver performance and road safety research is pertinent. Malaysia is well endowed with a road network that effectively covers the country.…”
Section: Introductionmentioning
confidence: 99%